2018
DOI: 10.1021/acs.iecr.8b03810
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Supported on Carbon Nanotubes Decorated Nickel Foam as the Catalytic Stirrer in Heterogeneous Hydrogenation of Polystyrene

Abstract: Carbon nanotubes supported palladium (Pd/CNTs) catalyst displayed excellent activity toward hydrogenation of polystyrene (PS) to produce polycyclohexylethylene (PCHE) with added commercial values. However, its application is limited by the costly catalyst filtration process and energy-consuming elevated agitation speed. Herein, a dense, homogeneous and strongly attached layer of CNTs was decorated on nickel foams and employed as the catalyst support for palladium nanoparticles. Structured catalyst (Pd/CNTs@NF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The palladium catalyst supported on carbon nanotubes decorated nickel foam was directly employed as the catalytic stirrer in a rotating foam stirrer reactor for polystyrene hydrogenation. The improved performance suggesting the enhanced liquid-solid mass transfer in the rotating foam stirrer reactor with the merits of eliminating the filtration operation [10]. While the entangled carbon nanotubes layer with open pores and the dense carbon layer beneath covered around the skeleton of nickel foam, the palladium catalyst supported on carbon nanotube modified nickel foam establish a hybrid hierarchical structure with large effective surface area and promoted the internal diffusion of large polystyrene coils [11].…”
Section: Carbon Nanotubes Supported Palladium Catalystmentioning
confidence: 99%
“…The palladium catalyst supported on carbon nanotubes decorated nickel foam was directly employed as the catalytic stirrer in a rotating foam stirrer reactor for polystyrene hydrogenation. The improved performance suggesting the enhanced liquid-solid mass transfer in the rotating foam stirrer reactor with the merits of eliminating the filtration operation [10]. While the entangled carbon nanotubes layer with open pores and the dense carbon layer beneath covered around the skeleton of nickel foam, the palladium catalyst supported on carbon nanotube modified nickel foam establish a hybrid hierarchical structure with large effective surface area and promoted the internal diffusion of large polystyrene coils [11].…”
Section: Carbon Nanotubes Supported Palladium Catalystmentioning
confidence: 99%
“…Polyurethane foam (∼60 PPI) was purchased from Shanghai QiTai Sponge Co., Ltd. Silica aerogel (∼99%) was provided by Guangzhou GBS high-tech and industry Co., Ltd. CNTs (outer diameter: ∼50 nm) were purchased from Chengdu Organic Chemicals Co., Ltd. Al­(NO 3 ) 3 ·9H 2 O, Mg­(NO 3 ) 2 ·6H 2 O, Fe­(NO 3 ) 3 ·9H 2 O, and decahydro­naphthalene (DHN) were offered by Sinopharm Chemical Reagent Co., Ltd. The palladium precursor Pd­(NO 3 ) 2 ·2H 2 O (Pd content: 39.5 wt %) and 1-octanol was provided by Adamas Reagent Co., Ltd. High-purity gases, including H 2 , N 2 , and C 2 H 4 were all purchased from Shanghai Siling Gas Co., Ltd. Commercial PS (GPPS-123) was purchased from Shanghai SECCO Petrochemical Co., Ltd., and its detailed information could be found in our previous work . All the reactants were used directly without further treatment.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Supercritical CO 2 (sc-CO 2 ) was introduced into the hydrogenation system to reduce the size of PS coils and solution viscosity. However, CO was formed via the reverse water–gas shift reaction as a result of the introduction of sc-CO 2 and inevitably caused the deactivation of Pd catalyst. , Another solution is the structural optimization of the macroporous of supports like silica hollow microspheres with size-tunable penetrating macroporous shells. , Still the challenge remains as the fine-powdered catalyst support needs to be separated from the viscous product solution after the hydrogenation process, which wastes the resource and hampers the industrialization . Previously, we proposed the application of structured CNTs modified nickel foam as supports for Pd nanoparticles (NPs) toward PS hydrogenation. Results suggested that Pd supported on CNTs decorated nickel foam catalyst (Pd/CNTs@NF) exhibited excellent activity owing to its wide open structure with abundant surface area facilitating the high dispersion of Pd active sites and the accessibility of PS to them, meanwhile the issue concerning catalyst separation could be conveniently solved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, a lot of effort has been made to overcome those problems. , Loading TS-1 to suitable support is a novel and facile method to prepare the monolithic TS-1. , The surface chemical properties and interaction between support and gels play a significant role in in situ crystallization . It has been reported that carbon nanotubes immobilized on nickel foam (CNT/NF) have been successfully applied to load TS-1 particles. The monolithic TS-1 is usually synthesized by the traditional hydrothermal method; however, this method produces the associated powder at the bottom of the crystallization autoclave, resulting in wastage of gels and templates. In addition, solvents occupied a lot of space in the autoclaves, greatly reducing the product yield. Therefore, it is very important to develop an effective and green strategy to synthesize monolithic TS-1. …”
Section: Introductionmentioning
confidence: 99%